A Compact Model for Generic MIS-HEMTs Based on the Unified 2DEG Density Expression - Zhang, Junbin (2016)
In this paper, the 2-D electron gas density (ns) and Fermi level (Ef) analytical expressions as an explicit function of the terminal biases that covers the strong- and moderate-inversion and subthreshold regions and scalable with physical parameters are developed. It is validated by the comparison with the (exact) numerical solutions for different device parameters, in which the device operating region may encompass one or two lowest sub-bands ( E0 and E1) in the triangular well. With the unified Ef model, a surface-potential (φs) based drain-current (Ids) model for the metal-insulator-semiconductor (MIS) high electron-mobility transistor (HEMT) is developed. Nonlinear source/drain access region resistances ( Rs and Rd) can also be modeled via a subcircuit, including an empirical Rs model for capturing the current-collapse effect. The compact drain-current model is shown to match the experimental data of MIS HEMTs very well in both subthreshold and strong-inversion regions, with smooth and symmetric behaviors and including the (dc) self-heating effect. It also models the corresponding MIS diode C-V using the same set of physical and minimum fitting parameters.